2019
DOI: 10.3390/ijms20102588
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-inflammatory Effects of Dietary Anthocyanins against Ulcerative Colitis

Abstract: Ulcerative colitis (UC), which is a major form of inflammatory bowel disease (IBD), is a chronic relapsing disorder of the gastrointestinal tract affecting millions of people worldwide. Alternative natural therapies, including dietary changes, are being investigated to manage or treat UC since current treatment options have serious negative side effects. There is growing evidence from animal studies and human clinical trials that diets rich in anthocyanins, which are pigments in fruits and vegetables, protect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 158 publications
2
80
0
1
Order By: Relevance
“…Phenolic compounds are well known for their antioxidant property. Furthermore, accumulating evidence has shown that polyphenols play a role in interfering with the inflammatory signaling pathway to modulate immune responses in the gut [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds are well known for their antioxidant property. Furthermore, accumulating evidence has shown that polyphenols play a role in interfering with the inflammatory signaling pathway to modulate immune responses in the gut [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…These results show that anthocyanins are able to protect the intestinal barrier by modulating tight junction-positive and -negative protein ratios, exemplifying the anti-colonic inflammation effects of anthocyanins from various fruits and vegetables (22,23). In addition, anthocyanins have high antioxidant abilities, attributable to the ability of their phenolic groups to donate electrons, or transfer electrons from hydrogen atoms, to quench free radicals.…”
Section: Anthocyanins Catechins Resveratrol and Chlorogenic Acidmentioning
confidence: 73%
“…As previously stated, one of the traditional uses of Fragaria is as an anti-inflammatory agent [61,62]. Most of the authors assign the anti-inflammatory properties to the presence of anthocyanins (the most representative being pelargonidin and cyanidin derivates) [75], molecules with known anti-inflammatory potential [76,77], demonstrated both in vitro and in vivo [78,79]. Similar to the other biomedical potential, the anti-inflammatory action is also correlated with the composition of different Fragaria species.…”
Section: Anti-inflammatory Propertiesmentioning
confidence: 99%